IMPLEMENTATION IOT APPLICATIONS FOR ELECTRICITY LOAD MONITORING AND CONTROL (JESII: Journal of Elektronik Sistem InformasI, 2023)
Human activities are strongly dependent on the use of electricity, making it a daily requirement. The basic electricity rate is currently rising, making electricity conservation necessary. In order to solve this problem, a centralized power load monitoring and control system that can be handled remotely utilizing Internet of Things (IoT) technologies is suggested in this study. The research project involves creating and putting into use a prototype system. An Intel Core i3 laptop, 4 GB of RAM, Windows 7 64-bit, the Arduino IDE program, and a Tools Set were the tools used in the study. A Microcontroller NodeMCU E12 WiFi, Relay Driver, LED indication, and PIR Sensor made up the components employed. The research method was broken down into eight stages, including a review of the literature, the formulation of a problem and an objective, the collecting of data, the design and use of media, the implementation of the results, the drawing of conclusions, and the preparation of a report. The functionality of each system component was tested, and the overall system performance was assessed, in order to examine the research findings. The results show that input, process, and output are the three essential components of the IoT application architecture for monitoring and regulating electrical loads in rooms. Four PIR sensors in the input area indicate the presence of people in the space. Â A microcontroller integrated with the NodeMCU 12E WiFi device is used in the process step. LED indicator lights in the output portion show the amount of load present in the space. Hardware and software components make up the implementation of the IoT application for tracking and managing electrical loads in rooms. The NodeMCU 12E microcontroller and a PIR sensor make up the hardware component, while Cayenne, an IoT service, and the Arduino IDE serve as the software components. The IoT application has overall performed well and according to design in monitoring and regulating the room's electrical demands.